Fæstedskatten – oprindelsen - Grundvad, Lars (Arkæologi i Slesvig-Archäologie in Schleswig, 2023)
The Viking Age gold hoard from Fæsted was discovered by amateur archaeologists and excavated by Sønderskov Museum in 2016 and has since grown by several additional artefacts. The hoard has been studied in several articles, some with more scholarly value than others. Three articles should be highlighted, which shed light on the hoard in different ways; an initial in-depth presentation of the find (Grundvad/Poulsen 2020), a typological analysis of the Jelling style‘s relationship to Gorm the Old and the Jelling dynasty‘s use of the Nordic styles, where the hoard and the artifacts are used as a case (Grundvad/ Knudsen 2017) and then an attempt to interpret the hoard as a religious deposition (Grundvad 2022; Grundvad in press). This article is the fourth in a planned series of analyses, each of which aims to illuminate the Fæsted hoard from different perspectives. Thus, the goal here is to ascertain the origin of the jewellry and artifacts from the treasure. It is clear though, that this is far from feasible to do with all objects. For some artifacts, unambiguous relationships are clear to see. For some of the other objects, a slightly bold interpretation of origin will be presented, where both distinctions are made to the Roman imperial jewellery seen in the iconographic sources and to the loot which the Vikings are known to have brought home from raids. Finally, the aim is to present what the different origins reveal and how the hoard of gold artifacts seems intentionally put together.